Analisis Faktor Internal Dan Eksternal Kinerja Penyuluh Pertanian Di Balai Penyuluh Pertanian Kecamatan Cerme Kabupaten Gresik - David Muhammad Adam; Raden Achmad Djazuli (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Performance can be defined as the work results achieved by an individual or group of individuals within an organization in accordance with their authority and responsibility to achieve organizational goals legally, without violating the law, and in accordance with moral and ethical norms. There are two factors that influence performance, namely: internal factors and external factors. In Gresik Regency, the role of the Agricultural Extension Center (BPP) as an institution that provides education and information to farmers is very important. One of the BPPs that is active in carrying out agricultural extension activities is the BPP of the Cerme District Agriculture Service. In this context, the performance of extension at the BPP Cerme District is highly dependent on a number of interacting factors, both internal and external factors. Based on the background description, the objectives of the PKL implementation are: 1) To analyze the performance of agricultural extension workers at the BPP of the Cerme District Agricultural Service. 2) To analyze internal and external factors of agricultural extension workers' performance at the BPP of the Cerme District Agricultural Service. This research was conducted at the Agricultural Extension Center (BPP) of the Cerme District Agricultural Service, Gresik Regency, with a period of implementation from March to August for 5 months. Based on the results found, it can be concluded that the performance of extension workers at the Cerme District Agricultural Extension Center is generally considered very good. This can be seen from the implementation of tasks that run according to the work program and responsibilities of each extension worker. Internal factors that influence performance include: motivation, competence/ability, attitude and work ethic, work experience, and communication. While External Factors that influence performance are: Organizational support and infrastructure, leadership style, social and cultural work environment, and government policies and incentive systems.